Effectiveness of Online Balanced Nutrition Education via Zoom on Knowledge and Attitudes of Junior High School Adolescents - Kamila Aisyah; Nenny Triastuti; Annisa Nurida (CV. CENDIKIA JENIUS INDONESIA, 2025)
Adolescence is a critical period characterized by rapid growth, hormonal changes, and increased nutritional needs. An imbalance in nutrient intake may lead to health problems such as anemia, undernutrition, and obesity. Digital media has the potential to serve as an effective platform for nutrition education tailored to adolescents. This study aimed to evaluate the effectiveness of online balanced nutrition education delivered via Zoom Meeting on the knowledge and attitudes of junior high school students in Surabaya. A quasi-experimental design with a pretest-posttest control group was employed. The sample consisted of 77 students aged 13–15 years from SMPN 46 and SMPN 48 Surabaya, selected purposively. The intervention involved a 120-minute balanced nutrition education session using visual presentations, videos, and infographics. Research instruments included a knowledge questionnaire (20 items) and an attitude questionnaire (15 statements). Data were analyzed using paired sample t-test and independent sample t-test with a significance level of p < 0.05. The results showed a significant increase in knowledge scores after the intervention (p = 0.000) and a positive shift in attitudes among most participants, particularly regarding the importance of fruit and vegetable consumption and the practice of healthy hygiene behaviors. In conclusion, online balanced nutrition education effectively improved adolescents’ knowledge and attitudes, and it is recommended to be implemented continuously with the involvement of schools and families to encourage better nutritional practices.